ANALYSIS OF ELEVENTH-GRADE VOCATIONAL HIGH SCHOOL STUDENTS PROBLEM-SOLVING ABILITY IN LINEAR PROGRAMMING - Sari, Nurfatma; Roza, Yenita; Yuanita, Putri (Jurnal Pendidikan Matematika dan IPA, 2025)
This research is motivated by the fact that problem-solving ability is a fundamental skill that students must possess. However, field observations indicate that students"™ problem-solving abilities in linear programming material remain relatively low. The aim of this study is to describe students' problem-solving abilities based on Polya's theory, which consists of four stages: understanding the problem, devising a plan, carrying out the plan, and reviewing the solution. This study employs a qualitative descriptive research design. The subjects of the study were 22 eleventh-grade students from the Accounting and Finance Expertise Program at Vocational high School (SMK) Negeri 1 Pagaran Tapah Darussalam. Data collection techniques included tests, interviews, and documentation. The test instrument consisted of essay questions assessing mathematical problem-solving abilities in linear programming material. The results of the study reveal that: (1) At the very good level, students were able to solve problems sequentially according to Polya"™s stages; (2) At the good level, students completed the stages in sequence but failed to explicitly state what was being asked in the problem and did not review their final solutions; (3) At the poor level, students exhibited calculation errors during the implementation stage of the problem-solving plan; (4) At the very poor level, students were unable to solve problems according to Polya"™s stages.